Current trends and future prospective in nanoremediation of heavy metals contaminated soils: A way forward towards sustainable agriculture - Temoor Ahmed (Elsevier, 2021)
Heavy metals (HMs) contamination in agricultural soils is a major concern for global food safety and human health. Although, various in-situ and ex-situ remediation methods have been used for the treatment of HMs contaminated soils, however, they also have many drawbacks viz., capital investment, toxicity, and environmental health hazards. Consequently, there is an urgent need to develop a novel method to ameliorate the toxicity of HMs in agricultural soils. In recent years, nanoparticles (NPs) have gained significant attention due to their potential applications in the environment and agriculture fields. Nanoremediation employs NPs that effectively reduce the contents of toxic HMs in the soil-plant system. Several studies have reported that the application of NPs in HMs-polluted soils, which reduced plant-available HMs concentration soils. However, the long-term efficiency of NPs immobilization is still unclear. Here, we provide details about the toxicity of HMs to environmental systems and potential applications NPs to alleviate the accumulation of HMs in agricultural soils. Finally, we present the mechanistic route of HMs-toxicity alleviation in plants by NPs application as well as their long-term efficiency and future prospects.